An observational study of patient characteristics and mortality following hypoglycemia in the community. Issue 1 (30th June 2015) - Elwen, Francesca R; Huskinson, Alice; Clapham, Linda; Bottomley, Matthew J; Heller, Simon R; James, Cathryn; Abbas, Afroze; Baxter, Paul; Ajjan, Ramzi A
Abstract : Objectives: Characterize patients with diabetes with severe hypoglycemia requiring emergency services intervention at home and investigate 12-month mortality. Research design and methods: Emergency services call-outs for hypoglycemia were recorded between 2005 and 2013 in an area covering 34 000 patients with diabetes. Patient characteristics were documented together with capillary blood glucose (CBG), glycated hemoglobin (HbA1c), and treatment for hypoglycemia; 12-month mortality and variables influencing survival were analyzed. Results: In 1835 episodes among 1156 patients, 45% had type 1 diabetes (68.2% males) and 44% had type 2 diabetes (49.4% males), with a minority unclassified. CBG at presentation (mean±SD) was 1.76±0.72 mmol/L in patients with type 1 diabetes and 1.96±0.68 mmol/L in patients with type 2 diabetes (p<0.0001), with a higher HbA1c in the former group (8.3±1.52% (67.5±16.4 mmol/mol) and 7.8±1.74% (61.6±19.0 mmol/mol), respectively; p<0.0001). A third of patients with type 2 diabetes were not on insulin therapy and displayed lower HbA1c compared with insulin users. Glucagon was used in 37% of patients with type 1 diabetes and 28% of patients with type 2 diabetes (p<0.0001). One-year mortality was 4.45% in type 1 diabetes and 22.1% in type 2 diabetes. Age and type of diabetes were predictive of mortality in multivariable analysis, whereas CBG levels/frequency of hypoglycemia had no effect. Conclusions: Severe hypoglycemia in the community is common with a male predominance in type 1 diabetes. Severe hypoglycemia in non-insulin treated patients with type 2 diabetes is associated with lower HbA1c compared with insulin users. Severe hypoglycemia appears to be associated with increased mortality at 12 months, particularly in type 2 diabetes.